2017
DOI: 10.1155/2017/6356751
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Fouling and Chemical Cleaning in Three Full-Scale Reverse Osmosis Plants Producing Demineralized Water

Abstract: Membrane fouling and cleaning were studied in three reverse osmosis (RO) plants. Feed water was secondary wastewater effluent, river water, and surface water. Membrane autopsies were used for fouling characterization. Fouling layer measurements included total organic carbon (TOC), adenosine triphosphate, polysaccharides, proteins, and heterotrophic plate counts. In all locations, membrane and spacer fouling was (bio)organic. Plant chemical cleaning efficiencies were evaluated from full-scale operational data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 27 publications
(53 reference statements)
0
23
0
1
Order By: Relevance
“…A similar finding was reported by Beyer et al, (2017). In this study [19], examining chemical cleaning at three full-scale RO plants, feed channel pressure drop improved by 10%, but permeability decreased by 5% and salt rejection remained unchanged, indicating a compaction of the fouling layer. It is also plausible that NaOH requires a longer contact time than urea to effectively restore membrane permeability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar finding was reported by Beyer et al, (2017). In this study [19], examining chemical cleaning at three full-scale RO plants, feed channel pressure drop improved by 10%, but permeability decreased by 5% and salt rejection remained unchanged, indicating a compaction of the fouling layer. It is also plausible that NaOH requires a longer contact time than urea to effectively restore membrane permeability.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the membrane surface morphology (SEM) and biofilm composition (EDX and FTIR) confirmed the presence of biological materials (biofouling) on the membrane modules. Cleaning of the membrane modules at the DECO plant with chemicals such as NaOH and urea is therefore a suitable cleaning strategy, since the reaction mechanism of both the cleaning agents results in the removal of organic fouling [19,38]. Preliminary laboratory studies confirmed the compatibility of urea with the polyamide membranes [23], where urea was not found to damage the polyamide layer of the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To restitute the initial performance of RO unit and control the fouling phenomenon [47], the Dow FilmTec TM company recommended to carry out a standard chemical cleaning, applying basic (1% 4Na-EDTA + 0.1% NaOH) and acidic (0.2% HCl) chemical solutions [26,31,48].…”
Section: Performance Assessment Of the Plant Normalized Datamentioning
confidence: 99%
“…Basic chemical agents including sodium hydroxide (NaOH) clean off organic fouling and biofouling by hydrolysis and solubilization; instead, acid agents including hydrochloric acid (HCl) disperse inorganic fouling, break up the composition of the bacterial cell wall and promote precipitation of proteins [24,32,47,49]. Concerning RO membranes, cleaning procedures involve various steps of high flow recirculation and soaking [31], enduring all over between 6.5 to 24 hours in period at a usual temperature of 35°C [32,47].…”
Section: Performance Assessment Of the Plant Normalized Datamentioning
confidence: 99%